VARIATIONS IN THE PHYSICAL CONDITION OF HOUSES WITH THE RISK OF TUBERCULOSIS IN THE WORKING AREA OF THE BILALANG HEALTH CENTER BOLAANG MONGONDOW NORTH SULAWESI - Rokot, Agus; Mokoginta, Hatima; Kabuhung, Anselmus; Katiandagho, Dismo; Kawatu, Yozua (Jurnal Locus Penelitian dan Pengabdian, 2023)
Mycobacterium Tuberculosis, generally attacks the lungs and outside the lungs. The house functions as a livable place to live. The house functions as a place to live, which is healthy and comfortable, a source of inspiration for its residents so that they can increase their productivity. House construction and an environment that does not meet health requirements are risk factors for disease transmission. Tuberculosis is closely related to the physical condition of the house. Research objective: to determine variations in the condition of the physical quality of the house with the risk of Tuberculosis. Type of Quantitative Research with a Case Control approach carried out during June-July 2023. The population is the community in eight villages in the work area of ??the Bilalang Health Center in 2022 who suffer from TB, namely 20 respondents with a control sample of 20 people, a total sample of 40 respondents. Implementation: observation, interviews, measurements of the physical variables of the respondent's house: residential density, humidity, lighting and ventilation. Data analysis using univariate, bivariate, Chi-Square test statistics. Test results, chi square there is a relationship between physical variations of houses and the risk of Tuberculosis in the work area of ??the Bilalang Bolaang Mongondow Community Health Center, North Sulawesi with residential density p value = 0.005 OR value 7.000 95 % CI (1.739-28.179), Humidity p value = 0.026 OR 5.571 95 % CI (1.420 – 21.860), lighting p value = 0.026 OR value 5.571 95 % CI (1.420 – 21.860), and ventilation p value = 0.009 OR value 8.500 95 % CI (1.861 – 38.817). In conclusion, there is a significant relationship between occupant density, humidity, lighting, house ventilation and the risk of Tuberculosis. Suggestion; For pulmonary TB sufferers, it is best to open the bedroom window to let sunlight enter, so that it is free of bacteria. Community Health Center officers provide education about the risks and prevention of tuberculosis.